The Forms of Intellectual Property Rights Waqf as a Part of Productive Waqf - Eva Mir'atun Niswah (Indonesian Academy of Social and Religious Research (IASRR), 2022)
The paradigm of productive waqf is contained in Waqf Regulation (Law Number 41 of 2004 Concerning Waqf). This regulation expands the scope of property in waqf which was previously only on fixed objects, now includes movable objects, both tangible and intangible. As an intangible movable object, IPR (Intellectual Property rights) is one of the waqf objects in this regulation. However, the forms of IPR waqf has not been explained on waqf regulations . So that, this paper will discuss the forms of IPR waqf as a part of productive waqf form. First, the absolute handover of IPR by the wakif to Nazir. In this form the nazir can manage IPR waqf by himself or licenses. Second, waqif can do his waqf of IPR for a certain period using a license or franchise